2019
DOI: 10.1371/journal.pone.0210315
|View full text |Cite
|
Sign up to set email alerts
|

A data-driven study of Chinese participants' social judgments of Chinese faces

Abstract: Social judgments of faces made by Western participants are thought to be underpinned by two dimensions: valence and dominance. Because some research suggests that Western and Eastern participants process faces differently, the two-dimensional model of face evaluation may not necessarily apply to judgments of faces by Eastern participants. Here we used a data-driven approach to investigate the components underlying social judgments of Chinese faces by Chinese participants. Analyses showed that social judgments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 16 publications
6
31
0
Order By: Relevance
“…Our study is one of several recent studies that have begun to utilize different statistical models and explore more dynamic theories of trait ratings 21,43,44 by exploring how the structure of trait ratings vary systematically. This growing body of work catalogues variations in trait ratings by target demographic 21,43,45 , target status 46 , target age 47 , perceiver knowledge 48 , and cultural factors 17,18 . Further, this growing body of work proposes dynamic theories of person perception and more flexible statistical models for capturing them 21,43,44,49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is one of several recent studies that have begun to utilize different statistical models and explore more dynamic theories of trait ratings 21,43,44 by exploring how the structure of trait ratings vary systematically. This growing body of work catalogues variations in trait ratings by target demographic 21,43,45 , target status 46 , target age 47 , perceiver knowledge 48 , and cultural factors 17,18 . Further, this growing body of work proposes dynamic theories of person perception and more flexible statistical models for capturing them 21,43,44,49 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the most comprehensive test of social evaluations of faces to date, including more than 11,000 participants. Participating research groups were recruited via the Psychological Science Accelerator project 25-27 . Previous studies compared two cultures to demonstrate regional differences 17,18 . By contrast, the scale and scope of our study allows us to generate the most comprehensive picture of the world regions to which the valence-dominance model does and does not apply.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has reported both common 3 and discrepant dimensions in different cultures 13,14,24,35,37 . To test the generalizability of our ndings, we conducted a second preregistered study to collect data across seven different regions of the world.…”
Section: Generalizability Across Different Countries and Regionsmentioning
confidence: 99%
“…Prior work 1,13,14,35,37 suggests that the various words people use to describe faces can be represented by two or three dimensions. Our ndings support the general idea of a low-dimensional space, but revealed four dimensions that differ from those previously proposed.…”
Section: Comparison With Existing Dimensional Frameworkmentioning
confidence: 99%
“…Further, it may matter a great deal who the observers are that make these judgments, as the specific dimensional structure that best accounts for social evaluations varies cross-culturally. Recent results suggest that Chinese observers, for example, appear to evaluate faces according to valence and competence rather than valence and dominance (Wang et al, 2019), which strongly suggests that the set of fundamental social judgments may vary with experience or culture. Further, Na et al (2015) demonstrated that while electability tends to be predicted well in Western populations using competence as a proxy, the same does not hold for Korean observers.…”
Section: Social Evaluation Of Face Imagesmentioning
confidence: 99%